The economic crisis as a game changer? Exploring the role of social construction in sustainability transitions - Derk Loorbach; Flor Avelino; Alex Haxeltine; Julia M. Wittmayer; Tim O'Riordan; Paul Weaver; René Kemp (Ecology and Society, 2016)
Continuing economic turbulence has fuelled debates about social and political reform as much as it has stimulated actions and initiatives aimed at a more fundamental transition of dominant economic systems. This paper takes a transition perspective to explore, from a Western European viewpoint, how the economic crisis is actually viewed through a variety of interpretations and responded to through a range of practices. We argue that framing societal phenomena such as the economic crisis as "symptoms of transition" through alternative narratives and actions can give rise to the potential for (seemingly) short-term pressures to become game changers. Game changers are then defined as the combination of: specific events, the subsequent or parallel framing of events in systemic terms by engaged societal actors, and (eventually) the emergence of (diverse) alternative narratives and practices (in response to the systemic framing of events). Game changers, when understood in these terms, help to orient, legitimize, guide, and accelerate deep changes in society. We conclude that such dynamics in which game changers gain momentum might also come to play a critical role in transitions. Therefore, we argue for developing a better understanding of and methodologies to further study the coevolutionary dynamics associated with game changers, as well as exploring the implications for governance.